Local effects of adipose tissue in psoriasis and psoriatic arthritis - Kruglikov IL; Wollina U (Dove Medical Press, 2017)
Ilja L Kruglikov,1 Uwe Wollina2 1Scientific Department, Wellcomet GmbH, Karlsruhe, 2Department of Dermatology and Allergology, Hospital Dresden-Friedrichstadt Academic Teaching Hospital of the Technical University of Dresden, Dresden, Germany Abstract: The structure and physiological state of the local white adipose tissue (WAT) located underneath the lesional psoriatic skin and inside of the joints affected by psoriatic arthritis play an important role in the pathophysiology of these diseases. WAT pads associated with inflammatory sites in psoriasis and psoriatic arthritis are, correspondingly, dermal WAT and articular adipose tissue; these pads demonstrate inflammatory phenotypes in both diseases. Such local WAT inflammation could be the primary effect in the pathophysiology of psoriasis leading to the modification of the local expression of adipokines, a change in the structure of the basement membrane and the release of keratinocytes with consequent epidermal hyperproliferation during psoriasis. Similar articular adipose tissue inflammation can lead to the induction of structural modifications and synovial inflammation in the joints of patients with psoriatic arthritis. Keywords: psoriasis, psoriatic arthritis, pathophysiology, adipose tissue, dermal adipocytes, articular adipose tissue